2022
DOI: 10.1097/corr.0000000000002392
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Outcomes After THA and TKA Are Substantially Mediated by Socioeconomic Disadvantage Both in Black and White Patients

Abstract: Background Demographic factors have been implicated in THA and TKA outcome disparities. Specifically, patients' racial backgrounds have been reported to influence outcomes after surgery, including length of stay, discharge disposition, and inpatient readmissions. However, in the United States, health-impacting socioeconomic disadvantage is sometimes associated with racial differences in ways that can result in important confounding, thereby raising the question of whether race-associated post-THA/TKA adverse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Another paper on a related theme this month found that although Black patients were more likely than White patients to experience safety-related complications of spine surgery, a substantial part of this finding—nearly half of it, for some endpoints—was attributable to elements of social disadvantage other than race, as measured by the Social Vulnerability Index [4]. This finding seemed consistent across the analyses published in this symposium that asked related questions in this way [6].…”
mentioning
confidence: 65%
“…Another paper on a related theme this month found that although Black patients were more likely than White patients to experience safety-related complications of spine surgery, a substantial part of this finding—nearly half of it, for some endpoints—was attributable to elements of social disadvantage other than race, as measured by the Social Vulnerability Index [4]. This finding seemed consistent across the analyses published in this symposium that asked related questions in this way [6].…”
mentioning
confidence: 65%
“…42,43 Devotion of resources to overcome language barriers and medical transportation effort may help reduce these disparities. 44,45 Our subanalysis of cost-center-specific charges identified charge differences of $2,110 for Black and $18,657 for Hispanic patients compared with White patients, although this difference was almost 10 times higher for Hispanic patients. Higher accommodation charges accounted for 86% of the difference for Black patients and may present a target for intervention.…”
Section: Discussionmentioning
confidence: 86%
“…Apart from acknowledging the existence of healthcare disparities, it is critical for us, as providers, to spread awareness and educate peers, our care teams, and patients about the existence of health disparities. Discussing articles such as Hadad et al's [4] with our peers and residents in a journal club and volunteering for community seminars in the underprivileged community to address fears and culture-related beliefs about the benefit of orthopaedic procedures such as total joint arthroplasty to treat end-stage arthritis are ways we can spread awareness about health inequity.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…Socioeconomic disparity is a big cause of healthcare disparities and is closely tied to racial disparities. A study in this month’s Clinical Orthopaedics and Related Research ® by Hadad et al [4] is an important contribution to our efforts to understand what really drives these disparities, rather than focusing—as so much earlier research has—on simplistic associations between race and outcomes of interest. The authors studied the relationship and interplay of race (Black versus White) and socioeconomic status, as determined by the Area Deprivation Index, with outcomes after TKA and THA.…”
Section: Where Are We Now?mentioning
confidence: 99%